Toxoptera citricidus (Kirkaldy, 1907) (Homoptera, Aphidoidea), the tropical citrus aphid in continental Portugal - Ilharco F.A.; Sousa-Silva C.R. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
Surveys aiming to detect the presence of T. citricidus in Portugal mainland have been carried out since 1963. The aphid was detected for the first time in Madeira Island in 1994 and in the mainland in 2003, in the north western region. In the years that followed the aphid could be always detected, and in some places even in the winter months. The infested area is slowly enlarging. The preferred host is C. lemon. Predators and parasitoids are present in the period of population growth. A macroscopic key is presented for the identification of the economically important Citrus aphids in Portugal.